Reduzir, reutilizar e retuítar: Instituto Akatu, comunicação ambiental e o discurso do consumo consciente do nas mídias sociais - Santos, Camila Silva (2019)
The environmental crisis, symbolized by the macro phenomenon of climate change, is perhaps the largest contemporary global social issue. Its discussion crosses all the socioeconomic contexts, in which the shift of the focus of concern from production to consumption has gained increasing visibility. In a network society, marked by communication mediated by new digital technologies and the hyperconnection statute, this discussion circulates intensely among the most diverse social actors, being present in the modern and popular platforms and websites of electronic social networks. Based on Environmental Sociology and Consumer Studies, from the perspective of Critical Discourse Analysis, this study seeks to characterize and analyze the Environmental Communication made by the Akatu Institute for Conscious Consumption in the socalled social media, in which this non-profit organization profitable is present, being very active in the effort to legitimize an environmentalist discourse with an appeal directed to “conscious consumption”. This discourse is implemented in different communicative modalities through the Internet, with emphasis on its participation in two of the main social networking platforms widely used in Brazil - Twitter and Facebook. For purposes of analysis, the research will prioritize a corpus delimited by the publications made by the Institute in their profiles in these two electronic "social networks", relying on data analysis applications, especially Nvivo, to encode posts made in the twelve months of the year. 2017. Of an essentially qualitative character, but without ignoring relevant quantitative aspects, in the first phase it established a comparison of Akatu's discursive strategy in both platforms, and then, in a second moment, to proceed with the discursive analysis itself, so as to understand constitutive and pragmatic aspects of this discursive matrix, especially in the scope of the attribution of responsibility, in the definition and delimitation of the problem of consumption and possible solutions suggested by the environmental communication practiced by the institute.